Machfudzil Asror IMPLEMENTASI MANAJEMEN BUDAYA PONDOK PESANTREN DALAM PENINGKATAN KECERDASAN SANTRI DI PONDOK PESANTREN AMANATUL UMMAH SIWALANKERTO SURABAYA : Program Studi Manajemen, Universitas Nahdlatul Ulama Sidoarjo *e-mail: machfudzil.asror1985@gmail.com - Machfudzil Asror (Universitas Nahdlatul Ulama Sidoarjo, 2019)
The purpose of this study is 1.) Describe the cultural management of Islamic boarding schools in Amanatul Islamic Boarding School Ummah Siwalankerto Surabaya. 2.) Describe the intelligence of the students of Amanatul Islamic Boarding School Ummah Siwalankerto Surabaya 3.) Describe the cultural management of boarding schools in improving the intelligence of students in the Islamic Boarding School of Amanatul Ummah Siwalankerto Surabaya. The method used in this research is to use qualitative methods that are descriptive, the data collection techniques are using observation, interview, documentation, and interview techniques. And the analysis of the data that we have done has obtained the following findings: First, the management of the Amanatul Ummah Islamic Boarding School among others creates an atmosphere of religious learning and time discipline. Secondly, the Amanatul Ummah Islamic Boarding School does not only emphasize the aspect of intellectual intelligence, but also the emotional and spiritual aspects of students are also highly considered. Third, in its implementation, the Islamic boarding school students must settle in the boarding school of Amanatul Ummah boarding school so that for 24 hours the students receive education and supervision from the educators of the Amanatul Ummah boarding school. Fourth, the curriculum used is the Al-Azhar Egyptian curriculum.